Demodulation and modulation of high bit data transmission in low voltage supply system - Abdullah, Rosmadi (2007)
Nowadays, we can found many technologies that have been developed for control applications. Power line communication (PLC) is one of the technologies that has been proved useful for control applications. It is widely use in home automation, automotive, and internet access applications. Up to date, there is no product found in the market use it for agricultural applications. Its potential for agricultural application is very promising. This study focuses on the development of a prototype using PLC system for control application in agricultural sector. On the sane token, X-10 is a well known technology used in home automation. This prototype uses the same technique in X-10 technology, but with a few improvement and modification to suit the control application in the agricultural sector. Graphical user interface (GUI) using Microsoft Visual Basic 6.0 software has been developed and functions as a switch to control electrical devices used in agricultural application remotely. Power line modem and controller for this system has been successfully fabricated at cheaper cost as compared to other systems sold in market. Today, farmers can have full control of their electrical machines by only pressing a single button on the graphical user interface.